Islamic Historical Studies: The Beginning of the Emergence of Islam and the Development of Islamic Culture in Southeast Asia - Abdul Azis; Sharfina Nur Amalina; Azharotunnafi Azharotunnafi (Riwayat: Educational Journal of History and Humanities, 2021)
Islamization basically occurs in various regions, one of which is the target of Islamization is a strategic area inhabited by the majority of Islam, namely Southeast Asia.  The news can be seen from the process of entering Islam in various ways, for example, one of which is by peaceful means, as stated in proselytizing, music art and various ways so that no violence or coercion is found. Islam entered Southeast Asia through trade channels which were sourced from various countries, one of which was from Arabia and India. The methodology in this article uses a descriptive qualitative approach in using historical methods. The researchers' findings in this research process include; (1) The process of arrival through trade routes that cross southeast Asia so that inter-people-to-people conflicts result in Islamization in this region; (2) The results of the study also reveal the fact that Islamization also occurs in the sectors of marriage, friendship and strong proselytizing. This article reveals that the fact of Islamization is very strong in Southeast Asian society.